Sosio Religius dalam Internalisasi Nilai Tasamuh dan Syura pada Kehidupan di Kampus IAI Tarbiyatut Tholabah - Hakim Nur; Sa’adi Sa’adi; Miftahuddin Miftahuddin (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The internalization of the values of tasamuh (tolerance) and syura (consultation) is an integral part of the academic culture that Islamic higher education institutions seek to build. However, there is still a gap between the idealism of the institutional vision and the reality of student social practices in campus life. This study aims to analyze the implementation of a socio-religious approach in the internalization of the values of tasamuh (tolerance) and syura (consultation) within the campus environment of IAI Tarbiyatut Tholabah Lamongan. This study employs a descriptive qualitative method with a phenomenological approach. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The results of the study indicate that efforts to internalize the values of tasamuh and syura have been carried out through the educational curriculum, student organization activities, and character development. However, there are still challenges in applying these values, such as group polarization, resistance to dialogue, and uneven involvement from the academic community. These findings differ from previous studies, which tended to emphasize the formal aspects of the curriculum without delving deeply into the social dynamics of students. This study contributes theoretically and practically to the development of more contextual strategies for internalizing Islamic values, and recommends strengthening the culture of consultation and collaborative training across campus elements.